Pengendalian Gulma Dengan Tanaman Sela Kacang Pada Budidaya Jagung Manis Tumpangsari - Setiawan, Agus Nugroho (Universitas Muhammadiyah Yogyakarta, 2005)
An research on weed control with legumes in sweet corn intercropping was conducted in Kasihan, Bantul District of Yogyakarta on February to June 2003. The experiment was aimed to study the role of legume crop to control weed growth in the intercropping of sweet corn. The experiment was arranged in a single factor randomized completely block design (RCBD) with three blocks as replication. The treatment was the kind of legumes i.e groundnut, mungbean and soybean planted with sweetcorn in the ratio of 1: 1, 1:2, and 1:3 to be compared to sole crop of sweet com and legumes. The result of this experiment showed that legumes existence reduced light intensity on soil surface. Presence of legumes as second crop with ratio up to 1:3 was significantly reduced the weed growth but not significantly influenced growth and yield of sweet corn. The higher the ratio of sweet corn-legumes, the achievement of legumes yield and land equivalent ratio were higher.